1996
DOI: 10.1515/znb-1996-0703
|View full text |Cite
|
Sign up to set email alerts
|

Eine neue Modifikation von Na2Zn2O3 / A New Modification of Na2Zn2O3

Abstract: A new modification of Na2Zn20 3 has been synthesized via solid state reaction. According to the single crystal structure determination, the compound crystallizes in the space group P432|2 (No. 96) with lattice parameters a = 6.1812(2), c = 9.4479(4) A, Z = 4. The structure consists of Z n 0 4 tetrahedra connected via edges and corners forming a threedimensional network. The structure can be described as an distorted anti spinel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…It crystallizes in the monoclinic system with space group P2 1 /c and lattice parameters of a = 5.82(0), b = 5.95 (2), c = 5.88(7)Å and β = 117.6 • [11]. Trinschek and Jansen [12] synthesized a new modification of the 1:2 compound by solid-state reaction. According to the single crystal structure determination, it crystallizes in the tetragonal system with space group P4 3 2 1 2 and lattice parameters of a = b = 6.1812 (2), c = 9.4479(4)Å. Trinschek and Jansen also synthesized the 1:1 compound [13] and the 5:4 compound [14] by reacting Na 2 O, which was produced in situ from Na 3 N 2 and NaNO 2 , with ZnO in the solid-state.…”
Section: Introductionmentioning
confidence: 99%
“…It crystallizes in the monoclinic system with space group P2 1 /c and lattice parameters of a = 5.82(0), b = 5.95 (2), c = 5.88(7)Å and β = 117.6 • [11]. Trinschek and Jansen [12] synthesized a new modification of the 1:2 compound by solid-state reaction. According to the single crystal structure determination, it crystallizes in the tetragonal system with space group P4 3 2 1 2 and lattice parameters of a = b = 6.1812 (2), c = 9.4479(4)Å. Trinschek and Jansen also synthesized the 1:1 compound [13] and the 5:4 compound [14] by reacting Na 2 O, which was produced in situ from Na 3 N 2 and NaNO 2 , with ZnO in the solid-state.…”
Section: Introductionmentioning
confidence: 99%
“…22,23) Kulakov et al 22) reported that under certain oxygen environment, the NaCu 2 O 2 phase is stable in the temperature interval 530 to 900 C. The rate of decomposition of NaCu 2 O 2 becomes significantly higher at temperatures over 900 C. There are oxozincates (such as Na 2 ZnO 2 , Na 2 Zn 2 O 3 , Na 10 Zn 4 O 9 , and K 2 Zn 3 O 4 ) have been reported in different chemical systems. [24][25][26][27][28] The compounds are metastable up to 750 C. Additionally since the sintering temperature is reduced, the evaporation of Na 2 O is greatly reduced and the chance for Na element to interact with CuO or ZnO would be greatly enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, this fact has allowed to prepare new metastable phases in the ternary system Na/Zn/O, which had previously been scanned carefully, putting special effort on synthesizing Na 2 ZnO 2 73. Employing the ANR, the new oxozinkates Na 10 Zn 4 O 9 54 as well as metastable Na 2 ZnO 2 55 and β‐Na 2 Zn 2 O 3 56 have been obtained, all featuring special structural properties. β‐Na 2 Zn 2 O 3 corresponds to an anti‐spinel structure, whereas Na 2 ZnO 2 and Na 10 Zn 4 O 9 are constituted of novel networks of linked tetrahedra (Figure 14).…”
Section: A Gallerymentioning
confidence: 99%